Becoming Latina, becoming Americana: shifting identities in Lara Rios’s chick lit - Maryam Mazloomian,; Raihanah M. M.,; Shahizah Ismail Hamdan, (Pusat Pengajian Bahasa dan Linguistik, FSSK, UKM, 2015)
This article examines the process of acculturation in two female members of a Mexican-American community as represented in Lara Rios’s chick lit novels: Becoming Latina in 10 Easy Steps (2006, 2013) and Becoming Americana (2006). The examination of the two chick lit novels is conducted on a trajectory of ecological systems of development as well as in the light of the psychosocial attitude, self-image, expectations and assumptions about becoming Americana or the reverse. The two heroines who reportedly met each other by chance narrated the turning points in their lives, experiencing the developmental passages through which their attitudes, beliefs, intentions, feelings had been assiduously expressed towards age, gender, family, friends, job, ethnic background, as well as, the desire to become American and/or relapsing into being Latina. The article also points out that secure transition through the psychosocial developmental stages demands the trust in self, feminine power, and the culture within the surrounding society in diaspora. Furthermore, the deeper aspects of the host culture require ‘firm feelings’ and ’self-confidence’ as important constituents of becoming Latino-American.